Dermatosis Neglecta Based on Exanthematous Drug Eruption Following Head Trauma: A Case Report and Literature Review - Shi L; Zhao J; Zeng L; Wang L; Zhang G (Dove Medical Press, 2023)
Liping Shi,1,2 Jiaqing Zhao,1,2 Linxi Zeng,1,2 Lihong Wang,3 Guoqiang Zhang1,2 1Department of Dermatology, The First Hospital of Hebei Medical University, Shijiazhuang, People's Republic of China; 2Candidate Branch of National Clinical Research Center for Skin Diseases, Shijiazhuang, People's Republic of China; 3Department of Dermatology, Luancheng People's Hospital, Shijiazhuang, People's Republic of ChinaCorrespondence: Guoqiang Zhang, The First Hospital of Hebei Medical University, 89 Donggang Road, Yuhua District, Shijiazhuang City, Hebei Province, People's Republic of China, Tel +8618633888122, Email zlx090702@163.comAbstract: Dermatosis neglecta (DN) is a rare psychogenic dermatosis. To our knowledge, this is the first reported case of DN based on exanthematous drug eruption. We report a 68-year-old Chinese male patient who presented with thick, yellowish-brown crusting on his face and scalp and scaly skin for 6 days. Dermoscopy revealed diffusely distributed yellow-green serescrust-like plaques with different sizes and uneven thickness on a red background, and some demonstrated dot or globular hemorrhages. We considered DN and exanthematous drug eruptions based on the combination of the clinical medication and the history before the rash.Keywords: cutaneous dirt-adherent, malassezia infection, drug allergy, autoantibody